2023
DOI: 10.7759/cureus.47670
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Long-Term Adverse Events of COVID-19 Vaccines: A One-Year Follow-Up Study From the Kurdistan Region of Iraq

Manhal A Abdulkader,
Muayad A Merza

Abstract: BackgroundThe administration of COVID-19 vaccines has been critical in controlling the spread of the virus. However, understanding the potential adverse events (AEs) associated with these vaccines is crucial for public health. While most previous studies observed only short-term AEs, this study aimed to investigate the immediate and long-term AEs following the first and second doses of Pfizer, AstraZeneca, and Sinopharm vaccines, providing valuable long-term insights. MethodologyA prospective, one-year, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The risks may vary depending on the number and frequency of COVID-19 vaccine doses. Whereas some authors have observed fewer AEs after the second dose [134], others have reported an increased incidence [116]. Sultana et al reported varying trends in AEs after the second dose for both mRNA products, albeit with a higher frequency of AEs following the second-dose administration of the Moderna vaccine [135].…”
Section: Analyses Of Serious Harms To Humansmentioning
confidence: 99%
“…The risks may vary depending on the number and frequency of COVID-19 vaccine doses. Whereas some authors have observed fewer AEs after the second dose [134], others have reported an increased incidence [116]. Sultana et al reported varying trends in AEs after the second dose for both mRNA products, albeit with a higher frequency of AEs following the second-dose administration of the Moderna vaccine [135].…”
Section: Analyses Of Serious Harms To Humansmentioning
confidence: 99%